NGANTEN KERIS SEBAGAI SALAH SATU UPAYA MEMBERIKAN KEPASTIAN HAK WARIS ANAK DALAM PERSPEKTIF HUKUM ADAT BALI - Pasek Suryawan; Benyamin Tungga; Putu Eka Trisna Dewi (VYAVAHARA DUTA, 2023)
Balinese people know a marriage tradition called Nganten Keris. Where a nganten keris marriage is a marriage carried out by a woman with a keris which is a symbol or substitute for the man in the marriage process. There are several factors that cause the occurrence of kris nganten. Among other things, because the groom was unable to attend, the groom was from a higher caste than the bride, and because the woman was pregnant outside of marriage and there was no man willing to marry the woman. Nganten keris is used as an effort to provide certainty about the status of the birth of a child. Because in Balinese customary law, the legal status of a child is determined at the birth of the child. Balinese customary law requires that in order to be an heir a child must be born in a valid marriage according to Balinese customary law. The research method used is normative research using literature studies related to Balinese customary law and Hinduism, in order to find answers to the problem of nganten keris which is used as an effort to provide legal certainty regarding children's inheritance rights in Balinese customary law. Keywords : Nganten Keris, Balinese Traditional Inheritance, Balinese Customary Law.